THE CORRELATION BETWEEN CUSTOMERS’ SATISFACTION AND BRAND LOYALTY TOWARD IM3 - Nuraini Nuraini Ratnaningtyas Amarsa (Journal of Business Studies and Management Review, 2019)
A high number of customer turnover rate and strict competition between cellular provider services companies make companies compete each other due to create loyal customer. One of the companies is IM3. The escalation of complaints on customer dissatisfaction make them start to switch to other cellular provider. Hence, this study aims to know the description of customer’s satisfaction, customer’s loyalty and the correlation between customer’s satisfaction and loyalty toward IM3. This study uses non-experimental design using correlational methodology. The result showed that there is significant relationship on high correlation value and customer’s satisfaction in which giving a more than a half of the total value of brand loyalty. The satisfaction aspect of IM3 customer which has the most correlation with brand loyalty is the aspect of price and feature. Most of the customer feel the performance of IM3 is tend to be matched with the expectation. Therefore, there is positive relationship between customer’s satisfaction and loyalty.